Synthesis of Naphtho and 4-Bromonaphthotriazole-Ribonucleosides Using Trimethylsilyl Triflate as a Catalyst - El-Baih, F.E.M.; El-Talasi, H.H.; Hijazi, A.A. (Asian Journal of Chemistry, 2016)
Treatment of 1-trimethylsilylnaphtho[2,3-d]-1,2,3-triazole (II) with 1-O-acetyl-2,3,5-tri-O-benzoyl-β-D-ribofuranose (III) in the presence of trimethylsilyl trifluoromethanesulphonate led to an anomeric mixture of the corresponding 1-(2,3,5-tri-O-benzoyl-α-D-ribofuranosly)-naphtho[2,3-d]-1,2,3-triazole (IV) and 1-(2,3,5-tri-O-benzoyl-β-D-ribofuranosly)-naptho[2,3-d]-1,2,3-triazole (V). Separation of the anomers was achieved by chromatographical means. Debenzoylation of (IV) and (V) led to the free nucleosides (VI) and (VII) respectively. Similarly a mixture of 1-(2.3,5-tri-Q-benzoyl-α) (XI) and 1-(2,3,5-tri-O-benzoyl-β-D-ribofuranosyl)-4-bromonaphtho[2,3-d]-1,2,3-triazole (XII) was prepared and separated by chromatographical means. Structural proofs are based on 1H, 13C NMR and MS spectra The ribosylation of naphtho[2,3-d]-1,2,3-triazole (I) by dry fusion method afforded a very low yield of the protected ribonucleosides (IV) and (V).